A Comparative Clinical Study on Evaluation of Therapeutic Efficacy of Bilva and Mustak in Grahani Vikara w.s.r to IBS. - Yadav, Vijay; Chandrasekhar, K; Morya , Gyan Chand (International Research Journal of Ayurveda & Yoga, 2023)
Background & objectives: Grahani is a disease of great clinical relevance in the modern era because of its direct link with the improper food habits and stressful lifestyle. According to modern science this disease can be understood under the context of Irritable bowel Syndrome (IBS) characterized by abdominal pain and altered bowel habits with no particular structural pathology of the gastrointestinal tract. Nowadays world is moving towards the system looking eagerly for newer and safer drugs. So, there was selected a commonest and cost effective drug in the management of Grahani, in the welfare of society. In the present study Apakva Bilva fruit pulp in the form of Choorna (powder) was selected in the reference of classical texts of Charak Samhita. Methods: A trail study was conducted in 40 patients fulfilling the criteria of Grahani and divided into two equal groups: Group A and Group B. Patients in Group A were treated with Apakva Bilvaphala churna 3gm with Takra(50ml) BID after food along with Pathya Ahara and Vihara.Patients in Group B were administered with Mustaka Kanda (Tubes) churna 3gm with Takra(50ml) BID after food along with Pathya Ahara and Vihara.It was used as a control group. The study was carried out for a period of one month. Subjective parameters of Muhur Baddha / Muhur Drava Mala Pravritti, Mala Swaroop: Durgandhita /Picchila Mala, Udgara Pravritti : Madhura / Tikta / Amla, Trishna, Arochaka,Vidaha were taken for study. Results: The trial produced significant result among patients of Group A with Group B in regard to relief in subjective parameters. Outcome of study showed that the drug has vital action in remission of the symptoms. Discussion & Conclusion: Thus, the study showed the effectiveness of Bilva Churna in alleviating symptoms of Grahani. in comparison to that of control drug Mustaka Churna.